Woke Capitalism : How Corporate Morality is Sabotaging Democracy - Rhodes, Carl, 1967- (Book collections on Project MUSE., 2021)
This book delves into the corporate takeover of public morality, or 'woke capitalism'. Discussing the political causes that it has adopted, and the social causes that it has not, it argues that this extension of capitalism has negative implications for democracy's future.